Current collector and energy storage device

By forming a current collector material with a bilateral metal cladding on the polymer film, the problems of low thermal reliability and poor adhesion of the current collector material in the prior art are solved, and the high reliability and low intermediate discharge voltage effects of the lithium-ion battery cell are achieved.

CN119764455APending Publication Date: 2025-04-04DUPONT ELECTRONICS INC +1

Patent Information

Application Number
CN202411393576.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-03
Filing Date
2024-10-08
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The current collector materials of existing lithium-ion batteries, especially copper laminates produced by plating, have problems of low thermal reliability and poor adhesion, and it is difficult to meet the high reliability needs of electronic devices.

Method used

A polymer film is used as the current collector material, and a polymer film with a bilateral metal cladding is formed by adhering the first metal layer and the second metal layer to the polymer film. The film contains conductive fillers to improve conductivity and improve adhesion by specific process treatments.

Benefits of technology

The low intermediate discharge voltage of the current collector material is realized, the thermal reliability and adhesion of the battery cell are improved, and the high reliability needs of electronic devices are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073109200000241
    Figure BDA0005073109200000241
Patent Text Reader

Abstract

Disclosed is a current collector and an energy storage device, the current collector comprising a polymer film, a first metal layer adhered to the polymer film, and a second metal layer adhered to the polymer film on a side opposite to the first metal layer, wherein the polymer film contains a conductive filler and has a surface resistivity of 1 megohm / square or less; the first metal layer and the second metal layer each have a thickness of 3 μm or less; when compared to untreated battery-grade copper foil, based on a standard lithium-ion battery half-cell test conducted at a temperature of 25° C. and a discharge rate of 2C or higher, the current collector has an intermediate discharge voltage that is at least 20% lower. The energy storage device comprises the above current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The field of the present disclosure is current collectors and energy storage devices. Background Art

[0002] Copper foil is commonly used as an anode current collector for energy storage devices such as lithium-ion batteries (LIBs) due to its high electrical conductivity, its good chemical stability, and its electrochemical stability at low potentials. A battery cell for a lithium-ion battery includes a positive electrode, a negative electrode, and a separator between the two electrodes. A conventional lithium-ion battery cell also includes a current collector typically consisting of a foil or mesh or a metallized plastic, wherein the metal consists of aluminum (for the cathode) and copper (for the anode). The cathode material is coated on the cathode current collector (such as aluminum foil), and the anode material is coated on the anode current collector (such as copper foil). The separator between the electrode layers is typically made of a porous plastic material, and an ion-conductive organic solvent is used as an electrolyte to saturate the other components, thereby providing a mechanism for ion conduction between the anode and the cathode. These layers are typically wound together into a can or stacked. The continued desire for thinner and lighter devices has challenged the continued use of metal foils in these applications.

[0003] Polymer-based current collectors (such as metal-clad laminates) can be used as substitutes for metal foil. Metal-clad laminates (such as copper-clad laminates) are used in various electronic components for flexible circuits and circuit packaging in electronic devices. Copper-clad laminates based on polyimide films are typically prepared in the following manner: lamination for metal thickness greater than 5 μm, or sputtering for metal thickness less than 5 μm. Plating (e.g., electrochemical plating or chemical plating) is an alternative method for producing laminates, which has received some attention, but it is not widely used to produce laminates with a copper thickness of less than 5 μm. In addition, it is generally believed that the reliability of plated polyimide copper laminates is lower than the customer standards for electronic devices, and therefore will not be suitable for use as current collectors.

[0004] Metal clad laminates produced by plating have traditionally had poor thermal reliability relative to metal clad produced by sputtering or lamination of copper foil. The highest reliability plated laminates use an electroless nickel seed layer. Adhesion between plated copper and polyimide films is challenging due to the presence of volatiles in the film, degradation of the film surface by plating chemistry, and the use of functional film materials that lack strong chemical bonding to copper, among other factors. DETAILED DESCRIPTION

[0005] In a first aspect, a current collector comprises a polymer film, a first metal layer adhered to the polymer film, and a second metal layer adhered to the polymer film on a side opposite to the first metal layer. The polymer film contains a conductive filler and has a surface resistivity of 1 megohm / square or less. The first metal layer and the second metal layer each have a thickness of 3 μm or less. When compared to untreated battery-grade copper foil, the current collector has an intermediate discharge voltage that is at least 20% lower based on a standard lithium-ion battery half-cell test performed at a temperature of 25°C and a discharge rate of 2C or higher.

[0006] The polymer film adhered to the metal layer can be used to form a current collector for an energy storage device. In one embodiment, the available polymer composition for the polymer film may include polyimide (PI), poly (amide-imide) (PAI), poly (ester-imide), poly (amide-ester-imide), polycarbonate (PC), polyethylene naphthalate (PEN), polystyrene (PS), poly (methyl methacrylate) (PMMA), polyethylene terephthalate (PET), glycol-modified polyethylene terephthalate (polyethylene terephthalate glycol, PETG), poly cyclohexylenedimethylene terephthalate (poly cyclohexylenedimethylene terephthalate glycol, PCTG), polyetherimide (PEI), polysulfone, polyethersulfone, polyarylsulfone, polyaryletherketone (PAEK) (such as polyetheretherketone (PEEK) and polyetherketoneketone (PEKK)), and cyclic olefin copolymers. In one embodiment, a polymer composition with an imide group is particularly available. Polymer compositions having imide groups and containing aromatic monomers are very thermally, chemically and electrochemically stable at low (anode) and high (cathode) potentials typically used in lithium-ion batteries.

[0007] Depending on the context, "diamine" as used herein is intended to mean: (i) unreacted form (i.e., diamine monomer); (ii) partially reacted form (i.e., one or more moieties of an oligomer or other polymer precursor derived from or otherwise attributable to the diamine monomer) or (iii) fully reacted form (one or more moieties of a polymer derived from or otherwise attributable to the diamine monomer). Depending on the specific embodiment selected in the practice of the invention, the diamine can be functionalized with one or more moieties.

[0008] Indeed, the term "diamine" is not intended to be limiting (or to be interpreted literally) with respect to the number of amine moieties in the diamine component. For example, (ii) and (iii) above include polymeric materials that may have two, one, or zero amine moieties. Alternatively, the diamine may be functionalized with additional amine moieties (in addition to the amine moieties at the monomer ends that react with the dianhydride to extend the polymer chain). Such additional amine moieties may be used to crosslink the polymer or to provide other functional groups to the polymer.

[0009] Similarly, the term "dianhydride" as used herein is intended to mean a component that reacts with (cooperates with) a diamine and that in combination is capable of reacting to form an intermediate (which can then be cured into a polymer). Depending on the context, "anhydride" as used herein can mean not only the anhydride moiety itself, but also a precursor to the anhydride moiety, such as: (i) a pair of carboxylic acid groups (which can be converted to anhydrides by dehydration or similar types of reactions); or (ii) an acyl halide (e.g., chloride) ester functional group (or any other functional group currently known or developed in the future) that can be converted to an anhydride functional group.

[0010] Depending on the context, "dianhydride" can mean: (i) an unreacted form (i.e., a dianhydride monomer, whether the anhydride functionality is in true anhydride form or in precursor anhydride form, as discussed in the preceding paragraphs); (ii) a partially reacted form (i.e., one or more portions of an oligomer or other partially reacted or precursor polymer composition reacted from or otherwise attributable to the dianhydride monomer) or (iii) a fully reacted form (one or more portions of a polymer derived from or otherwise attributable to the dianhydride monomer).

[0011] According to the specific embodiment selected in the practice of the present invention, dianhydride can be functionalized with one or more parts.In fact, term "dianhydride" is not intended to limit (or explain literally) the number of the anhydride part in the dianhydride component.For example, (i), (ii) and (iii) (in the above paragraph) include organic substances that can have two, one or zero anhydride parts, depending on whether the anhydride is in precursor state or reaction state.Alternately, the dianhydride component can be functionalized with additional anhydride type part (except reacting with diamine to provide the anhydride part of polymer).This type of additional anhydride part can be used for cross-linked polymers or for providing other functional groups to polymers.

[0012] Any of many polymer manufacturing processes can be used to prepare polymer films. It will be impossible to discuss or describe all possible manufacturing processes that can be used for the practice of the present invention. It should be understood that the monomer system of the present invention can provide the above-mentioned favorable properties in various manufacturing processes. The composition of the present invention can be manufactured as described herein and can use any conventional or unconventional manufacturing technology to easily manufacture in any of the many (possibly countless) ways of those of ordinary skill in the art.

[0013] Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, suitable methods and materials are described herein.

[0014] When amount, concentration or other value or parameter is given as range, preferred range, or a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the range is disclosed separately. When numerical ranges are listed herein, unless otherwise stated, the range is intended to include its endpoints, and all integers and fractions within the range. It is not intended that the scope of the present invention is limited to the specific values ​​listed when limiting the range.

[0015] When describing certain polymers, it should be understood that sometimes applicants refer to these polymers by the monomers used to make them or the amounts of monomers used to make them. Although such descriptions may not include specific names used to describe the final polymer or may not contain terms that define the product in a process, any such reference to monomers and amounts should be interpreted to mean that the polymer is made from those monomers or that amount of monomers, and to the corresponding polymers and compositions thereof.

[0016] Unless otherwise stated, the materials, methods, and examples herein are illustrative only and not intended to be limiting.

[0017] As used herein, the terms "comprises," "comprising," "includes," "including," "has," "having," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a method, process, article, or apparatus that includes a list of elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such method, process, article, or apparatus. In addition, unless expressly stated to the contrary, "or" refers to an inclusive or and not to an exclusive or. For example, a condition A or B is satisfied by any of the following: A is true (or present) and B is false (or absent), A is false (or absent) and B is true (or present), and both A and B are true (or present).

[0018] In addition, "a / an" is used to describe the elements and components / parts of the present invention. This is done only for convenience and to give a general sense of the present invention. This description should be interpreted as including one / kind or at least one / kind, and the singular also includes the plural, unless it is obvious that it is otherwise intended.

[0019] It should be understood that, although the terms first, second, third, etc. can be used to describe different elements, components, regions, layers and / or parts in this article, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish an element, component, region, layer and / or part from another element, component, region, layer and / or part. Therefore, the first element, component, region, layer and / or part can be referred to as the second element, component, region, layer and / or part without departing from the teaching content of the present invention. Similarly, the terms "top" and "bottom" are only relative to each other. It should be understood that when elements, components, layers, etc. are inverted, the "bottom" before inversion will be the "top" after inversion, and vice versa. When an element is referred to as "on" or "arranged on" another element "on" another element, it means to be positioned on or under the object part, rather than essentially meaning to be positioned on the upper side of the object part based on the direction of gravity, and it can be directly on other elements or intermediate elements may exist between them. In contrast, when an element is referred to as being “directly on” or “disposed directly on” another element, there are no intervening elements present.

[0020] In addition, it should be understood that when an element, component, region, layer and / or section is referred to as being "between" two elements, components, regions, layers and / or sections, it can be the only element, component, region, layer and / or section between the two elements, components, regions, layers and / or sections, or one or more intervening elements, components, regions, layers and / or sections may also be present. Organic solvents

[0021] Useful organic solvents for synthesizing the polymers of the present invention are preferably capable of dissolving the polymer precursor materials. Such solvents should also have a relatively low boiling point, such as less than 225° C., so that the polymer can be dried at moderate (i.e., more convenient and less costly) temperatures. Boiling points of less than 210° C., 205° C., 200° C., 195° C., 190° C., or 180° C. are preferred.

[0022] Available organic solvents include: N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), methyl ethyl ketone (MEK), N,N'-dimethyl-formamide (DMF), dimethyl sulfoxide (DMSO), tetramethyl urea (TMU), glycol ethyl ether, diethylene glycol diethyl ether, 1,2-dimethoxyethane (monoethylene glycol dimethyl ether), diethylene glycol dimethyl ether (diglyme), 1,2-bis-(2-methoxyethoxy)ethane (triethylene glycol dimethyl ether), γ-butyrolactone and bis-(2-methoxyethyl) ether, tetrahydrofuran (THF), ethyl acetate, hydroxyethyl acetate, glycol monoacetate, acetone and mixtures thereof. In one embodiment, preferred solvents include N-methylpyrrolidone (NMP) and dimethylacetamide (DMAc). Diamine

[0023] In one embodiment, an aromatic diamine can be used to form a polymer having an imide group. The aromatic diamine can include a fluorinated aromatic diamine such as 2,2'-bis(trifluoromethyl)benzidine (TFMB), 2,2'-bis-(4-aminophenyl)hexafluoropropane, 4,4'-diamino-2,2'-trifluoromethyl diphenyl ether, 3,3'-diamino-5,5'-trifluoromethyl diphenyl ether, 9,9'-bis(4-aminophenyl)fluorene, 4,4'-trifluoromethyl-2,2'-diaminobiphenyl, 4,4'-oxy-bis[2-trifluoromethyl)aniline](1 ,2,4-OBABTF), 4,4'-oxy-bis[3-trifluoromethyl)aniline], 4,4'-thiobis[(2-trifluoromethyl)aniline], 4,4'-thiobis[(3-trifluoromethyl)aniline], 4,4'-sulfoxyl-bis[(2-trifluoromethyl)aniline], 4,4'-sulfoxyl-bis[(3-trifluoromethyl)aniline], 4,4'-keto-bis[(2-trifluoromethyl)aniline], 1,1-bis[4'-( 4'-amino-2'-trifluoromethylphenoxy)phenyl]cyclopentane, 1,1-bis[4'-(4'-amino-2'-trifluoromethylphenoxy)phenyl]cyclohexane, 2-trifluoromethyl-4,4'-diaminodiphenyl ether; 1,4-(2'-trifluoromethyl-4',4'-diaminodiphenyloxy)benzene, 1,4-bis(4'-aminophenoxy)-2-[(3',5'-ditrifluoromethyl)phenyl]benzene(6F-amine), 1,4-bis[2'-cyano-3'( "4-aminophenoxy)phenoxy]-2-[(3',5'-ditrifluoro-methyl)phenyl]benzene (6FC-diamine), 3,5-diamino-4-methyl-2',3',5',6'-tetrafluoro-4'-trifluoromethyl diphenyl ether, 2,2-bis[4(4-aminophenoxy)phenyl]phthalein-3',5'-bis(trifluoromethyl)aniline (6FADAP) and 3,3',5,5'-tetrafluoro-4,4'-diamino-diphenylmethane (TFDAM).

[0024] Other useful diamines may include 4,4'-diaminobiphenyl, 4,4"-diaminoterphenyl, 4,4'-diaminobenzanilide (DABA), 4,4'-diaminophenylbenzoate, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenylmethane (MDA), 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), 4,4'-bis(4-aminophenoxy)biphenyl (BAPB), 4,4'-diaminodiphenyl ether (ODE ...ether (ODE), 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone A), 3,4'-diaminodiphenyl ether, 4,4'-isopropylidene diphenylamine, 2,2'-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 3,3'-dimethyl-4,4'-diaminobiphenyl, 4-aminophenyl-3-aminobenzoate, bis(p-β-amino-tert-butylphenyl)ether, p-bis-2-(2-methyl-4-aminopentyl)benzene. In one embodiment, the diamine is a triamine, such as N,N-bis(4-aminophenyl)-n-butylamine, N,N-bis(4-aminophenyl)methylamine or N,N-bis(4-aminophenyl)aniline.

[0025] Other useful diamines may include 1,2-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene (RODA), 1,2-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1-(4-aminophenoxy)-3-(3-aminophenoxy)benzene, 1,4-bis-(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1-(4-aminophenoxy)-4-(3-aminophenoxy)benzene, 2,2-bis(4-[4-aminophenoxy]phenyl)propane (BAPP), and 2,2'-bis(4-phenoxyaniline)isopropylidene.

[0026] Other useful diamines may include p-phenylenediamine (PPD), m-phenylenediamine (MPD), 2,5-dimethyl-1,4-diaminobenzene, 2,5-dimethyl-1,4-phenylenediamine (DPX), 1,4-naphthalenediamine, 1,5-naphthalenediamine, 1,5-diaminonaphthalene, m-phenylenediamine, and p-phenylenediamine.

[0027] Other useful diamines for forming polymers with imide groups can include aliphatic diamines such as 1,2-diaminoethane, 1,6-diaminohexane (HMD), 1,4-diaminobutane, 1,5-diaminopentane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane (DMD), 1,11-diaminoundecane, 1,12-diaminododecane (DDD), 1,16-hexadecanediamine, 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, trans-1,4-diaminocyclohexane (CHDA), isophoronediamine (IPDA), bicyclo[2.2.2]octane-1,4-diamine, and combinations thereof. Other aliphatic diamines suitable for practicing the present invention include those having six to twelve carbon atoms or a combination of longer chain diamines and shorter chain diamines, as long as both ductility and flexibility of the polymer are maintained. Long chain aliphatic diamines can provide increased flexibility.

[0028] Other useful diamines for forming polymers with imide groups may include alicyclic diamines (which may be fully or partially saturated), such as cyclobutane diamines (e.g., cis- and trans-1,3-diaminocyclobutane, 6-amino-3-azaspiro[3.3]heptane, and 3,6-diaminospiro[3.3]heptane), bicyclo[2.2.1]heptane-1,4-diamine, isophorone diamine, and bicyclo[2.2.2]octane-1,4-diamine. Other alicyclic diamines may include cis-1,4-cyclohexane diamine, trans-1,4-cyclohexane diamine, 1,4-bis(aminomethyl)cyclohexane, 4,4'-methylenebis(cyclohexylamine), 4,4'-methylenebis(2-methyl-cyclohexylamine), bis(aminomethyl)norbornane. Dianhydride

[0029] In one embodiment, aromatic dianhydrides can be used to form polymers with imide groups. The dianhydride can be used in its tetraacid form (or as a mono-, di-, tri- or tetraester of tetraacid), or as its diester acyl halide (chloride). However, in some embodiments, the dianhydride form may be preferred because it is generally more reactive than acids or esters.

[0030] Examples of suitable aromatic dianhydrides include 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2-(3',4'-dicarboxyphenyl)-5,6-dicarboxybenzimidazole dianhydride, 2-(3',4'-dicarboxyphenyl)-5,6-dicarboxybenzoxazole dianhydride, 2-(3',4'-dicarboxyphenyl)-5,6-dicarboxybenzothiazole dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,3 ,3',4'-benzophenonetetracarboxylic acid dianhydride, 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride (BTDA), 2,2',3,3'-biphenyltetracarboxylic acid dianhydride, 2,3,3',4'-biphenyltetracarboxylic acid dianhydride, 4,4'-thio-diphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)sulfoxide dianhydride (DSDA), bis(3,4-dicarboxyphenyloxadiazole-1, 3,4)-p-phenylene dianhydride, bis(3,4-dicarboxyphenyl)-2,5-oxadiazole-1,3,4-dianhydride, bis(3',4'-dicarboxydiphenyl ether)-2,5-oxadiazole-1,3,4-dianhydride, 4,4'-oxydiphthalic anhydride (ODPA), bis(3,4-dicarboxyphenyl) sulfide dianhydride, bisphenol A dianhydride (BPADA), bisphenol S dianhydride, bis-1,3-isobenzofurandione, 1,4-bis (4,4'-oxyphthalic anhydride)benzene, bis(3,4-dicarboxyphenyl)methane dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, 1,3-bis-(4,4'-oxydiphthalic anhydride)benzene, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and 9,9-bis(trifluoromethyl)-2,3,6,7-xanthenetetracarboxylic anhydride.

[0031] Other useful dianhydrides may include 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, bicyclo-[2,2,2]-octene-(7)-2,3,5,6-tetracarboxylic acid-2,3,5,6-dianhydride, cyclopentadienyltetracarboxylic dianhydride, ethylenetetracarboxylic dianhydride, pyromellitic dianhydride (PMDA), tetrahydrofurantetracarboxylic acid dianhydride, anhydride, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-tetrachloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, phenanthrene-1,8,9,10-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, benzene-1,2,3,4-tetracarboxylic dianhydride and thiophene-2,3,4,5-tetracarboxylic dianhydride.

[0032] In one embodiment, the dianhydride used to form the polymer having an imide group may include an alicyclic dianhydride, such as cyclobutane-1,2,3,4-tetracarboxylic dianhydride (CBDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), hexahydro-4,8-ethano-1H,3H-benzo[1,2-c:4,5-c']difuran-1,3,5,7-tetraone (BODA), 3-(carboxymethyl)-1,2,4-cyclopentanetricarboxylic acid 1,4:2,3-dianhydride (TCA), and meso-butane-1,2,3,4-tetracarboxylic dianhydride.

[0033] In one embodiment, wherein the polymer further comprises an aromatic amide component, suitable additional diphosphonic acid chlorides for forming the polymer may include terephthaloyl chloride (TPCI), isophthaloyl chloride (IPCI), biphenyl dichloride (BPCI), naphthaloyl chloride, terphenyl dichloride, 2-fluoro-terephthaloyl chloride, and trimellitic anhydride.

[0034] In one embodiment, the poly(amide-ester-imide) can be produced from polyols, which can be reacted with carboxylic acids or ester halides to produce ester linkages.

[0035] The diol component can be almost any alcohol diol containing two esterifiable hydroxyl groups. It can also include a mixture of suitable diols. Suitable diols for use herein include, for example, ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, and the like.

[0036] The polyol component can be almost any polyol containing at least 3 esterifiable hydroxyl groups, so as to provide the advantages of the synthetic method described above of the present invention. A mixture of such polyols can be suitably adopted. Suitable polyols include, for example, tris (2-hydroxyethyl) isocyanurate, glycerol, 1,1,1-trimethylolethane, 1,1,1-trimethylolpropane, and mixtures thereof.

[0037] In some cases, useful diamine and dianhydride monomers contain ester groups. Examples of these monomers include diamines such as 4-aminophenyl-4-aminobenzoate and 4-amino-3-methylphenyl-4-aminobenzoate, and dianhydrides such as p-phenylene bis(trimellitate) dianhydride.

[0038] In some cases, useful diamine and dianhydride monomers contain amide groups. Examples of these monomers include diamines such as 4,4'-diaminobenzamide (DABAN), and dianhydrides such as N,N'-(2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diyl)bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxamide) and N,N'-(9H-fluorene-9-ylidenedi-4,1-phenylene)bis[1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxamide].

[0039] Higher order copolymers having imide groups may include any of the monomers described above. Imidization catalyst

[0040] In one embodiment, an imidization catalyst (sometimes referred to as an "imidization promoter") can be used as a conversion chemical, which can help reduce the imidization temperature for forming a polymer with an imide group and shorten the imidization time. The polyamic acid casting solution of the present invention includes a polyamic acid solution combined with a certain amount of conversion chemicals. It is found that the conversion chemicals that can be used in the present invention include, but are not limited to: (i) one or more dehydrating agents and / or promoters, such as aliphatic anhydrides (acetic anhydride, trifluoroacetic anhydride, propionic anhydride, monochloroacetic anhydride, bromoadipic anhydride, etc.) and aromatic anhydrides; and (ii) one or more imidization catalysts, such as aliphatic tertiary amines (triethylamine, etc.), aromatic tertiary amines (dimethylaniline, N, N-dimethylbenzylamine, etc.) and heterocyclic tertiary amines (pyridine, α-, β-, γ-methylpyridine, 3,5-lutidine, 3,4-lutidine, isoquinoline, etc.) and guanidine (e.g., tetramethylguanidine). In one embodiment, the imidization catalyst does not include diazoles. Other available dehydrating agents can include diacetyl oxide, butyryl oxide, benzoyl oxide, 1,3-dichlorohexyl carbodiimide, N, N-dicyclohexyl carbodiimide, benzenesulfonyl chloride, thionyl chloride and phosphorus pentachloride. In certain embodiments, dehydrating agent can also act as catalyst to enhance the reaction kinetics of imidization. Anhydride dehydrating material is typically used in a slightly molar excess of the amount of amic acid groups present in polyamic acid solution. In one embodiment, the amount of dehydrating agent used is typically about 2.0 to 4.0 moles / equivalent polyamic acid units. Generally, a considerable amount of tertiary amine catalyst is used. The ratio of these catalysts and their concentration in polyamic acid solution will affect imidization kinetics and film properties. Polymer film can have an imidization catalyst present in the polymer film in an amount in the range of 1 part / billion parts (ppb) to 1wt%, 10ppb to 0.1wt% or 100ppb to 0.01wt%. Conductive filler

[0041] In one embodiment, the conductive filler may include metals (such as gold, silver, copper, etc.), conductor mixed metal oxides (such as cuprates, superconducting oxides, indium tin oxides, antimony tin oxides, mixed titanium / tin / zirconium oxides, etc.), organic compounds (such as polyaniline, polythiophene, polypyrrole, polyphenylene vinylene, polydialkylfluorene), carbon black, graphite, graphene, multi-walled and single-walled carbon nanotubes and other nanotube structures, and carbon nanofibers. In one embodiment, the conductive filler may be an inorganic filler, an organic filler, or a mixture thereof.

[0042] In one embodiment, the conductive filler is carbon black. In one embodiment, the conductive filler is selected from the group consisting of acetylene black, super wear-resistant furnace black, conductive furnace black, conductive groove carbon black, carbon nanotubes, carbon fibers, fine thermal black and mixtures thereof. For carbon black, oxygen complexes on the surface of carbon particles act as an electrical insulating layer. Therefore, low volatile content is generally desired for high conductivity. However, the difficulty of dispersing carbon black also needs to be considered. Surface oxidation enhances the depolymerization and dispersion of carbon black. In some embodiments, when the conductive filler is carbon black, the carbon black has a volatile content of less than or equal to 1%. Other fillers

[0043] In one embodiment, other fillers for polymer film can include other inorganic and organic fillers not described above for conductive fillers.Inorganic fillers can include thermally conductive fillers, such as metal oxides, inorganic nitrides and metal carbides.In one embodiment, inorganic fillers can include diamond, clay, talc, sepiolite, mica, dicalcium phosphate, metal oxides (including magnetic metal oxides, transparent conductor oxides and gas phase metal oxides).In one embodiment, inorganic fillers can include inorganic oxides, such as oxides of silicon, aluminum, zinc and titanium, hollow (porous) silicon oxides, antimony oxides, zirconium oxides, indium tin oxides, antimony tin oxides, mixed titanium / tin / zirconium oxides, and one or more binary, ternary, quaternary and higher oxides of cations selected from silicon, titanium, aluminum, antimony, zirconium, indium, tin, zinc, niobium and tantalum.In one embodiment, particle composites (e.g., single or multiple core / shell structures) can be used, wherein in one particle, one oxide encapsulates another oxide.

[0044] In one embodiment, the inorganic filler may include other ceramic compounds such as boron nitride, aluminum nitride, ternary or higher order compounds containing boron, aluminum and nitrogen, gallium nitride, silicon nitride, aluminum nitride, zinc selenide, zinc sulfide, zinc telluride, silicon carbide and combinations thereof, or higher order compounds containing multiple cations and multiple anions, and may include oxycarbides and oxynitrides.

[0045] In one embodiment, the filler for the polymer film may have a median particle size d in the range of 0.1 to 10 μm, 0.1 to 5 μm, 0.2 to 5 μm, or 0.2 to 3 μm. 50 The filler size can be determined using a laser particle size analyzer, wherein the filler is dispersed in an organic solvent (optionally with the aid of a dispersant, an adhesion promoter, and / or a coupling agent). Median particle size d 50 It is the equivalent spherical diameter based on the median volume distribution of particles. If the median particle size is less than 0.1 μm, filler particles may tend to agglomerate or become unstable in organic solvents for polymer manufacturing. If the median particle size of the agglomerated particles exceeds 10 μm, the dispersion of the filler component in the polymer film may be too uneven (or inappropriately large for film thickness). The relatively uneven dispersion of the filler component in the film may lead to poor mechanical elongation of the film, poor flexure life of the film and / or low dielectric strength. In one embodiment, the filler may need to be ground and filtered in large quantities to break up unwanted particle agglomerations, as typically done when trying to disperse some fillers into a polymer matrix. Such grinding and filtering may be expensive and may not remove all unwanted agglomerates. In one embodiment, the average aspect ratio of the filler may be 1 or greater. In certain embodiments, the filler is selected from the group consisting of: needle-shaped fillers (needle-shaped), fibrous fillers, flaky fillers, polymer fibers, and mixtures thereof. In one embodiment, the filler can have an aspect ratio of at least 1, at least 2, at least 4, at least 6, at least 8, at least 10, at least 12, at least 15, at least 25, at least 50, at least 100, at least 200, or at least 300 to 1.

[0046] In one embodiment, the filler includes a mixture or blend of fillers having any number of particle types, particle sizes, and particle shapes, wherein the mixture or blend may have the same type of filler or different types of fillers.

[0047] In one embodiment, the filler can be coated with a coupling agent. For example, the filler particles can be coated with aminosilane, phenylsilane, acrylic or methacrylic coupling agents derived from the corresponding alkoxysilane. The trimethylsilyl surface capping agent can be introduced into the particle surface by the reaction of the filler with hexamethyldisilazane. In one embodiment, the filler can be coated with a dispersant. In one embodiment, the filler can be coated with a combination of a coupling agent and a dispersant. Alternatively, the coupling agent, dispersant or a combination thereof can be directly incorporated into the polymer film and not necessarily applied to the filler. Polymer film

[0048] In one embodiment, the polymer film as a polyimide film can be produced by combining diamine and dianhydride (monomer or other polyimide precursor forms) with a solvent to form a polyamic acid (polyamic acid) (also referred to as polyamic acid (polyamide acid)) solution. Dianhydride and diamine can be combined in a molar ratio of about 0.90 to 1.10. The molecular weight of the polyamic acid formed therefrom can be regulated by regulating the molar ratio of dianhydride to diamine.

[0049] In one embodiment, the polyamic acid casting solution is derived from a polyamic acid solution. The polyamic acid casting solution and / or the polyamic acid solution are combined with conversion chemicals, such as: (i) one or more dehydrating agents, such as aliphatic anhydrides (acetic anhydride, etc.) and / or aromatic anhydrides; and (ii) one or more catalysts, such as aliphatic tertiary amines (triethylamine, etc.), aromatic tertiary amines (dimethylaniline, etc.) and heterocyclic tertiary amines (pyridine, picoline, isoquinoline, etc.). Anhydride dehydration materials are usually used in molar excess compared to the amount of amic acid groups in polyamic acid. The amount of acetic anhydride used is typically about 2.0 to 4.0 moles / equivalent (repeating unit) of polyamic acid. Typically, a considerable amount of tertiary amine catalysts are used. Then the filler dispersed or suspended in the solvent as described above is added to the polyamic acid solution.

[0050] In one embodiment, the polyamic acid solution is dissolved in an organic solvent at a concentration of about 5.0 or 10 weight percent to 15, 20, 25, 30, 35 or 40 weight percent. In one embodiment, a slurry comprising a conductive filler is prepared, wherein the slurry has a conductive filler content in the range of 0.1 to 70, 0.5 to 60, 1 to 55, 2 to 50 or 5 to 45 weight percent. The slurry may or may not be ground using a ball mill to reach a desired particle size. The slurry may or may not be filtered to remove any remaining large particles. The polyamic acid solution may be made by methods well known in the art. The polyamic acid solution may or may not be filtered. In certain embodiments, the solution is mixed with a filler slurry in a high shear mixer. When a polyamic acid solution is made with a slightly excessive amount of diamine, an additional dianhydride solution may or may not be added to increase the viscosity of the mixture to a desired level for film casting. The amount of the polyamic acid solution and the filler slurry may be adjusted to achieve a desired load level in the cured film. In some embodiments, the mixture is cooled to below 10°C and mixed with the converting chemical prior to casting.

[0051] The solvated mixture (polyamic acid casting solution) can then be cast or applied to a support (such as an endless belt or a rotating drum) to obtain a partially imidized gel film. Alternatively, it can be cast on a polymer support such as PET, other forms of Polyimide film (e.g., HN or E film) or other polymer support. The gel film can be peeled from the drum or belt, placed on a tenter, and cured in an oven using convection and radiant heat to remove the solvent and complete the imidization to a solid level greater than 98%. The film can then be separated from the support, oriented (such as by tentering), and continued heating (drying and curing) to provide a polyimide film.

[0052] Useful methods for producing polyimide films can be found in U.S. Pat. Nos. 5,166,308 and 5,298,331, which are incorporated herein by reference for all teachings therein. Many variations are possible, such as, (a) A method in which a diamine component and a dianhydride component are mixed together in advance, and then the mixture is added to a solvent in portions while stirring. (b) A method in which a solvent is added to a stirred mixture of diamine and dianhydride components. (The opposite of (a) above) (c) A method in which a diamine is dissolved separately in a solvent, and then a dianhydride is added thereto at a ratio that allows the reaction rate to be controlled. (d) A method in which a dianhydride component is dissolved separately in a solvent, and then an amine component is added thereto at a ratio that allows control of the reaction rate. (e) A method in which a diamine component and a dianhydride component are separately dissolved in solvents, and then these solutions are mixed in a reactor. (f) A method in which a polyamic acid having an excess amine component and another polyamic acid having an excess dianhydride component are preformed and then reacted with each other in a reactor, particularly in such a manner as to produce a non-random or block copolymer. (g) A method in which a specific portion of the amine component and the dianhydride component are first reacted, and then the remaining diamine component is reacted, or vice versa. (h) A method in which a conversion chemical (catalyst) is mixed with polyamic acid to form a polyamic acid casting solution and then cast to form a gel film. (i) A method wherein the components are added partly or all in any order to partly or all of the solvent, further wherein part or all of any component may be added as a solution in part or all of the solvent. (j) A method in which one of the dianhydride components is first reacted with one of the diamine components to obtain a first polyamic acid. The other dianhydride component is then reacted with the other amine component to obtain a second polyamic acid. The amic acids are then combined in any of a number of ways prior to film formation.

[0053] In one embodiment, the mixture of solvation (polyamic acid casting solution) can be mixed with the crosslinked precursor, and then cast to form a polymer film. In one embodiment, the polymer film contains a crosslinked polymer in the range of 80wt% to 99wt%. In certain embodiments, the polymer film contains between any two of the following and includes any two crosslinked polymers: 80wt%, 85wt%, 90wt%, 95wt% and 99wt%. In another embodiment, the polymer film contains a crosslinked polymer of 91wt% to 98wt%.

[0054] In one embodiment, the cross-linking reaction includes chemical compounds, such as reactive amines, that can participate in the chemical reaction that cross-links the polymer chains in the film. In one embodiment, heat can be used to cross-link the polymer. In one embodiment, irradiation with a light source can be used to cross-link the polymer through a photo-initiated process. In one embodiment, additional reactive chemicals can be used to cross-link the polymer. In one embodiment, any combination of these methods can be used to cross-link the polymer.

[0055] The crosslinking of polymers can be determined by various methods. In one embodiment, the gel fraction of a polymer can be determined by using a balanced swelling method, comparing the weight of the dry film before and after crosslinking. In one embodiment, the crosslinked polymer can have a gel fraction in the range of 20% to 100%, 40% to 100%, 50% to 100%, 70% to 100%, or 85% to 100%. In one embodiment, the crosslinked network can be identified using rheological methods. The formation of a crosslinked network can be confirmed using oscillation time sweep measurements at specific strains, frequencies, and temperatures. Initially, the loss modulus (G") value is higher than the storage modulus (G') value, indicating that the polymer solution behaves like a viscous liquid. Over time, the formation of a crosslinked polymer network is demonstrated by the intersection of the G' and G" curves. The intersection (called the "gel point") indicates when the elastic component exceeds the viscosity to dominate.

[0056] In one embodiment, first conductive filler is dispersed in solvent to form slurry.Then slurry is dispersed in polyamic acid solution.In one embodiment, the concentration of conductive filler relative to polyimide (in final film) is based on the gross weight of polymer film in the range of 5wt% to 65wt%, 5wt% to 50wt%, 10wt% to 40wt% or 15wt% to 35wt%.In one embodiment, the concentration of conductive filler relative to polyimide (in final film) is based on the gross weight of polymer film for at least 5wt%, at least 10wt%, at least 15wt%, at least 20wt% or at least 25wt%.The composition of cured film can be calculated by the composition of the component in the mixture, excluding DMAc solvent (which is removed during curing) and considering removing water during polyamic acid is converted into polyimide.When using conductive filler, as the concentration of filler increases, the conductivity of polyimide film also increases. In one embodiment, the conductive polymer film can have a surface resistivity of 1 megohm / square or less, 0.5 megohm / square or less, 0.1 megohm / square or less, or 50,000 ohms / square or less. Those skilled in the art will appreciate that in addition to loading level, characteristics of the conductive fillers, such as particle size, morphology, aspect ratio, surface oxidation, etc., will affect the surface resistivity of the polymer film containing them.

[0057] In one embodiment, filler slurry is blended with polyamic acid solution to form the polyamic acid casting solution filled using high shear mixing to complete. In this embodiment, if there is a filler exceeding 65 weight percents in the final film, the film may be too brittle, and may not have enough flexibility to form independent, mechanically tough, flexible sheets. In addition, if the filler exists with a level less than 5 weight percents, the film formed therefrom may not have sufficient conductivity.

[0058] In one embodiment, the casting solution may further comprise any of a number of additives such as processing aids (eg, oligomers), antioxidants, light stabilizers, flame retardant additives, antistatic agents, heat stabilizers, UV absorbers, or various reinforcing agents.

[0059] In one embodiment, a coextrusion process can be used to form a multilayer polymer film with two or more layers, such as a three-layer polymer film with an inner core layer sandwiched between two outer layers. In this process, for a three-layer polyimide film, the finished polyamic acid solution is filtered and pumped to a slit die, where the stream is separated in a manner to form the first outer layer and the second outer layer of the three-layer coextruded film. In some embodiments, the second stream of the polymer is filtered and then pumped to a casting die in a manner to form an intermediate polymer core layer of the three-layer coextruded film. The solution flow rate can be adjusted to achieve a desired layer thickness. In one embodiment, the polymer composition and filler content of the first and second outer layers are the same, and in another embodiment, the polymer composition and / or filler content of the first and second outer layers are different. In some embodiments, the polymer composition and filler content of the core layer can be the same or different from the polymer composition and filler content of one or both of these outer layers.

[0060] In one embodiment, the multilayer film is prepared by extruding the first outer layer, the core layer and the second outer layer simultaneously. In certain embodiments, these layers are extruded by a single-cavity or multi-cavity extrusion die. In another embodiment, the multilayer film is produced using a single-cavity die. If a single-cavity die is used, the laminar flow of the flow should have a sufficiently high viscosity to prevent the mixing of the flow and provide uniform stratification. In certain embodiments, the multilayer film is prepared by casting from a slit die onto a moving stainless steel belt. In one embodiment, for a polymer with an imide group, the belt is then passed through a convection oven to evaporate the solvent and partially imidize the polymer to produce a "green" film. The green film can be peeled off from the casting tape and rolled up. The green film can then be passed through a tenter oven to produce a fully cured polymer film. In certain embodiments, during tentering, shrinkage can be minimized by constraining the film along the edges (i.e., using clips or pins).

[0061] In one embodiment, the outer layer of the present invention may also be applied to the core layer during an intermediate manufacturing stage in making a polymer film, such as to a gel film or a green film.

[0062] When forming the polymer containing imide, the term "gel film" refers to a polyamic acid sheet, which is loaded with volatiles, mainly solvents, to the extent that the polyamic acid is in a state of gel swelling or rubber-like, and can be formed in a chemical conversion process. The volatile content is usually in the range of 70% to 90% by weight of the gel film, and the polymer content is usually in the range of 10% to 30% by weight of the gel film. The final film becomes "self-supporting" at the gel film stage. It can be peeled off from the support to which it is cast, and heated to the final curing temperature. The gel film usually has a ratio of amic acid to imide between 10:90 and 50:50, most often 30:70.

[0063] The gel film structure can be prepared by the method described in U.S. Patent No. 3,410,826. This patent discloses mixing a chemical conversion agent and a catalyst such as a lower fatty acid anhydride and a tertiary amine into a polyamic acid solution at low temperature. This is followed by casting the polyamic acid solution onto a casting drum in the form of a film. After casting, the film is gently heated at, for example, 100°C to activate the conversion agent and the catalyst so as to convert the cast film into a polyamic acid / polyimide gel film.

[0064] Another type of polymer film is "raw film", which is part polyamic acid and part polyimide for polyimide film, and can be formed in a thermal conversion process. Raw film usually contains about 50% to 75% by weight of polymer and 25% to 50% by weight of solvent. Usually, it should be strong enough to be basically self-supporting. Raw film can be prepared by casting polyamic acid solution into film form onto a suitable support such as a casting drum or belt and removing the solvent by gentle heating at up to 150°C. A low proportion of amic acid units (e.g., up to 25%) in the polymer can be converted into imide units.

[0065] The application of the polymer film of the present invention can be achieved in any number of ways. Such methods include using slot die coating, dip coating or wet roller coating film, followed by metering with a scraper, scraper roller, squeeze roller or air knife. The coating can also be applied by brushing or spraying. By using such technology, both single-sided and double-sided coated laminates can be prepared. In the preparation of the structure coated on both sides, the coating can be applied to both sides of the polymer simultaneously or successively before the curing and drying stages of the polymer are carried out.

[0066] The thickness of the polymer film can be adjusted according to the intended purpose or end application specifications of the film.In one embodiment, the polymer film has a total thickness in the range of 1 to 300 μm, 2 to 200 μm, 5 to 150 μm, 10 to 100 μm, or 20 to 80 μm.

[0067] In one embodiment, for a two-layer or three-layer polymer film, the core layer has a thickness in the range of 0.75 to 225 μm, 1.5 to 150 μm, 3.75 to 112.5 μm, or 7.5 to 75 μm, and the one or more outer layers each have a thickness in the range of 0.25 to 75 μm, 0.5 to 50 μm, 1.25 to 37.5 μm, or 2.5 to 25 μm. In one embodiment, for a three-layer film, the thickness of the outer layers can be the same or different. current collector

[0068] In one embodiment, a current collector for an energy storage device may include a polymer film and a metal layer adhered to the polymer film. The current collector provides a way to transport charge (electricity) to an external circuit. However, in LIBs, current collectors are passive components, meaning they do not participate in the Li + Ion embedding reaction. Therefore, thin and light materials are preferably used for current collectors so that the weight energy density and volume energy density of the battery cell can be maintained high. These materials should have ion insulation and conductivity and maintain good chemical and electrochemical stability in the electrolyte during battery operation. Other requirements include providing a mechanically strong framework for the battery cell construction and should adhere well to the electrode slurry. In one embodiment, the current collector may include a polymer film having a metal layer adhered to both sides of the polymer film.

[0069] The current collector can be formed into a polymer film with a double-sided metal clad layer by any number of well-known processes. In one embodiment, a metal plating process can be used to form a metal clad layer with a polymer film (such as a polyimide film). In one embodiment, the polyimide film includes a thermoplastic polyimide layer. The metal layer can be formed on the thermoplastic polyimide layer of the polymer film by plating a thin metal layer. In one embodiment, the thin metal layer can be 10 μm or less, 5 μm or less, 3 μm or less, or 1 μm or less. By forming a metal layer on a polymer film using a plating process, a smoother interface can be formed between the current collector and the electrode. Conventional lamination of metal foil to polymer film relies on the surface roughness of the foil to provide good adhesion to the polymer film, but a roughness greater than the thickness of the thin metal layer may also be required.

[0070] In one embodiment, the polymer film can be bonded to the first metal layer and the second metal layer in a plating process to form a polymer film of a double-sided metal clad. The plating process may include chemical plating followed by electrolytic plating. A chemical plating process is used to form an initial metal layer that is generally less than 250nm or sufficient to provide uniform conductivity on the surface. The metal layer is then deposited to a desired thickness using an electrolytic plating process, providing a preferred Cu grain structure for good conductivity. In one embodiment, before forming the metal layer, the surface of the polymer film to be plated can be plasma treated. Therefore, the polymer film of the metal clad formed includes the polymer film and two thin conductive layers. In one embodiment, for a multilayer polymer film, a thermoplastic polymer layer is used as an outer layer in combination with a metal layer, so that strong adhesion between the polymer film and the metal layer can be achieved, regardless of the smoothness of the interface between the layers, and no additional primer or adhesive layer is used therebetween.

[0071] In other embodiments, other metal plating processes can be used to form a seed layer before electroplating. In one embodiment, atomic layer deposition (ALD) can be used to form a conductive seed layer of a metal (such as Pd or Ag) before electroplating. In one embodiment, a physical vapor deposition or sputtering process can be used to bond the polymer film to the metal layer. Physical vapor deposition occurs when a seed layer is deposited from a solid to a polymer film by evaporating a solid source material under vacuum conditions. In one embodiment, chemical vapor deposition can be used to bond the polymer film to the metal layer. In this process, the deposited material enters the deposition chamber in the gas phase.

[0072] In one embodiment, the polymer film can be bonded to the first metal layer by electrochemically depositing the metal layer directly on the polymer film (direct metallization). The term "direct electrochemical deposition of a metal layer" or "direct plating" on a polymer film means forming and building a metal layer on a polymer film using an electrolytic plating process without first forming an initial metal layer on the polymer film using an electrolytic plating process. Removing this seed layer from the process makes direct metallization faster and less expensive than conventional methods for making copper cladding. Energy storage device

[0073] In one embodiment, a current collector having a polymer film and a first metal layer and a second metal layer adhered to the polymer film can be used in energy storage devices such as lithium ion batteries, capacitors, supercapacitors, fuel cell units, and redox flow batteries. Any energy storage device in which the conductivity of the current collector can be used to complete a circuit and deliver power to an external device can benefit from using a current collector having a polymer film and a metal layer adhered to the polymer film. For example, a lithium ion battery cell includes a positive electrode (cathode), a negative electrode (anode), and a separator, at least one of which, preferably all of which, is in ionic conductive contact with an electrolyte solvent.

[0074] In one embodiment, the electrolyte solvent can be combined with one or more electrolytes, which will provide ions to the electrolyte, thereby making it ionically conductive. Suitable electrolytes include low molecular weight lithium salts and ionic polymers (called ionomers). Suitable low molecular weight lithium salts include both organic salts and inorganic salts, such as LiPF6, LiBF4, LiClO4, LiAsF6, LiN(SO2CF3)2, LiN(SO2CF2CF3)2, LiC(SO2CF3)3, etc. The molar concentration of lithium ions in the electrolyte solution can be 0.1 to 4.0M, with a preferred range of 0.5 to 2.0M. When the ionic species is an ionomer, it may still be necessary to add a certain amount of low molecular weight lithium salt to the electrolyte solvent at a concentration ranging from 0.01 to 1.0M.

[0075] In one embodiment, the electrolyte solvent may include acyclic and cyclic organic carbonates, primarily dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethylene carbonate (EC), and fluoroethylene carbonate (FEC), phosphorus-containing compounds such as trimethyl phosphate (TMP), tris(2,2,2-trifluoroethyl) phosphate (TFP), tris(2,2,2-trifluoroethyl) phosphite (TTFPi), bis(2,2,2-trifluoroethyl) methyl phosphonate (TFMP), (ethoxy) pentafluorocyclotriphosphazene (PFPN), and (phenoxy) pentafluorocyclotriphosphazene (FPPN), and monoesters such as methyl acetate (MA), ethyl acetate (EA), methyl formate (MF), methyl propionate (MP), ethyl propionate (EP), and γ-butyrolactone (GBL). Most commonly, these electrolyte solvents are used in combinations comprising cyclic organic carbonates (typically EC or PC) and acyclic carbonates (typically DMC, DEC, or EMC). In practice, it has been found that these combinations achieve an excellent combination of desirable properties (such as high ionic conductivity and relatively low volatility over a wide temperature range) while achieving excellent life and performance in lithium-ion batteries.

[0076] In one embodiment, the cathode comprises a cathode active material such as a lithium-containing transition metal oxide or phosphate capable of absorbing and releasing lithium ions to a capacity of greater than 100 mAh / g, such as LiCoO2, LiNiO2, Li(Ni,Co)O2, Li(Ni,Co,Mn)O2, LiMn2O4, LiV3O8, Li(Ni,Mn)O4, LiFePO4, LiMnPO4, LiCoPO4, and LiVPO4F. In another embodiment, the cathode active material can be a Li / Li + The material exhibits a capacity of greater than 30 mAh / g over a potential range greater than 4.6 V compared to the reference electrode. In other embodiments, the electrochemical cell is charged to a comparative Li / Li + The reference electrode is greater than or equal to 4.00V, 4.10V, 4.20V, 4.30V, 4.35V, 4.40V, 4.45V, 4.5V, 4.55V or a potential greater than 4.6V. An example of such a cathode active material is a stable manganese cathode comprising a lithium-containing manganese composite oxide having a spinel structure as a cathode active material. U.S. Patent Application Publication No. 2016 / 0087307A1 discloses a wide range of cathode active materials and is incorporated herein by reference.

[0077] The cathode active material can be prepared using a method such as the hydroxide precursor method described by Liu et al. (J. Phys. Chem. C [Journal of Physical Chemistry C] 13: 15073-15079, 2009). In this method, a hydroxide precursor is precipitated from a solution containing the required amount of manganese, nickel and other desired one or more metal acetates by adding KOH. The resulting precipitate is dried and then reacted with the required amount of LiOH.H2O in oxygen at about 800°C to about 950°C for 3 to 24 hours. Alternatively, the cathode active material can be prepared using a solid phase reaction method or a sol-gel method as described in U.S. Pat. No. 5,738,957. A cathode containing a cathode active material can be prepared by, for example, mixing an effective amount of the cathode active material (e.g., about 70 wt % to about 97 wt %), a polymer binder (e.g., polyvinylidene fluoride), and conductive carbon in a suitable solvent (e.g., N-methylpyrrolidone) to produce a paste, which is then coated onto a current collector and dried to form a cathode.

[0078] In one embodiment, the anode comprises an anode active material capable of storing and releasing lithium ions. Examples of suitable anode active materials include silicon, lithium metal, lithium alloys (such as lithium-aluminum alloys, lithium-lead alloys, lithium-silicon alloys, lithium-tin alloys, etc.); carbon materials, such as graphite and mesophase carbon microbeads (MCMB); phosphorus-containing materials, such as black phosphorus, MnP4 and CoP3; metal oxides, such as SnO2, SnO and TiO2; nanocomposites containing antimony or tin, such as nanocomposites containing antimony; oxides of aluminum, titanium or molybdenum; carbon and lithium titanate. In one embodiment, the anode active material is lithium titanate, graphite, lithium alloys, silicon, and combinations thereof. In another embodiment, the anode is graphite. In one embodiment, the graphite-based active material is MCMB (available from Osaka Gas Chemical Co., Ltd., Japan) or carbon fiber (Melblon, milled carbon fiber, available from Petoca Materials, Ltd., Japan), both of which are capable of achieving a reversible lithium insertion capacity of greater than 280 mAh / g. Other suitable carbon-based active materials for the anode include graphite flakes, polycrystalline graphite (PCG), petroleum coke, hard carbon, and natural graphite.

[0079] The anode containing the anode active material can be prepared by methods similar to those described above for the cathode, wherein, for example, a binder such as vinyl fluoride copolymer or styrene butadiene rubber is dissolved or dispersed in an organic solvent or water, and then mixed with an active conductive material to obtain a paste. The paste is then applied to a current collector. The paste is preferably dried by heating so that the active material is bonded to the current collector. Suitable anode active materials and anodes are commercially available from companies such as Hitachi NEI Inc. in Somerset, New Jersey, and Farasis Energy Inc. in Hayward, California.

[0080] In one embodiment, the lithium ion battery also includes a porous separator between the anode and the cathode. The porous separator is used to prevent short circuits between the anode and the cathode. The porous separator is typically composed of a single or multilayer sheet of a microporous polymer such as polyethylene, polypropylene, polyamide or polyimide, or a combination thereof. The pore size of the porous separator is large enough to allow ions to be transmitted to provide ion-conducting contact between the anode and the cathode, but small enough to prevent the anode from directly contacting the cathode, or preventing contact due to particle penetration or dendrite formation. Examples of porous separators suitable for use herein are disclosed in U.S. Pat. No. 8,518,525, which is incorporated herein by reference.

[0081] The housing of the lithium-ion battery can be any suitable container that accommodates the lithium-ion battery components described above. Such a container can be made into the shape of a button battery unit, a small or large cylinder, a square shell or a soft bag.

[0082] In one embodiment, the energy storage device (such as a lithium-ion battery) can be used for grid storage or as a power source in various electronic devices such as computers, cameras, radios or power tools, various communication devices, or various transportation devices (including motor vehicles, cars, trucks, buses or airplanes). Various battery cell configurations can be used for different battery applications, including pouch battery cells, prismatic battery cells, button battery cells, cylindrical battery cells, wound prismatic battery cells, wound pouch battery cells, etc.

[0083] The advantageous properties of the invention may be observed by reference to the following examples which illustrate but do not limit the invention. Unless otherwise indicated, all parts and percentages are by weight. Examples Test Method granularity

[0084] The particle size of the filler particles in the slurry was measured by laser diffraction using a particle size analyzer (Mastersizer 3000, Malvern Instruments, Inc., Westborough, Mass.) DMAc was used as the carrier fluid. Surface resistivity

[0085] To measure surface resistivity, a Loresta AXMCP-T370 (Mitsubiushi Chemical Analytech Co., LTD, Kanagawa, Japan) equipped with a PSP linear 4-point probe was used to measure surface resistivity at 15 locations evenly distributed on a polymer film piece of approximately 12" x 12", following ASTM D257. The 15 measurements were averaged to determine the surface resistivity of the film. The surface resistivity can be measured on either side of the polymer film. Battery Evaluation

[0086] A battery test system (CT3002A, Landt Instruments, Vestal, NY) was used to evaluate the battery performance in the half-cell configuration. All measurements were performed at 25°C. + / Li 0 Charging and discharging were performed between 2V and 0.002V. The cells were activated for one cycle at 0.05C before cycling under constant current conditions. In all cases, the charge rate used for cell evaluation was 0.1C. The discharge rate was varied from 0.1C to 5C in each subsequent cycle. The C-rate is based on the capacity of the graphite electrodes in the cell. During the charge / discharge cycle, the intermediate discharge voltage is the voltage at which half of the charge capacity of the electrode is depleted at a given current or C-rate. Carbon black slurry

[0087] For some embodiments, a carbon black slurry is prepared to provide a conductive filler, which is composed of 9.5 wt% carbon black powder ( 7055U, Aditya Birla Group, Marietta, Georgia), 17.25 wt% polyamic acid (13.06 wt% PMDA / ODA and 4.19 wt% PMDA / BPDA / / ODA / PPD) and 73.25 wt% DMAc. Grinding and high shear mixing are used for complete uniform particle dispersion of the slurry. The median particle size of the filler particles is d 50 (equivalent spherical diameter based on the median volume distribution of particles) is less than 1 μm. Multilayer polymer film

[0088] The polyamic acid solution for producing core layer and outer layer is prepared separately by chemical reaction between monomers of appropriate molar equivalent in dimethylacetamide (DMAc) solvent.Typically, the diamine dissolved in DMAc is stirred under nitrogen, and the dianhydride in solid form is added in the time period of several minutes.Stirring is continued to obtain the polyamic acid of maximum viscosity.In certain embodiments, 15wt%-60wt% carbon black slurry is added in the polyamic acid solution and mixed using a high shear mixer.The composition of the cured film is calculated by the composition of the components in the mixture, excluding DMAc solvent (which is removed during the curing process) and considering removing water during the conversion of polyamic acid into polyimide.The viscosity is regulated by the amount of dianhydride in the control polyamic acid composition.

[0089] Multilayer films are cast by coextrusion. Three separate polyamic acid polymer streams are simultaneously extruded through a multi-cavity extrusion die onto a heated moving belt to form a coextruded three-layer polyimide film. The thickness of the polyimide core layer and the top and bottom thermoplastic polyimide outer layers are adjusted by varying the amount of polyamic acid fed to the extruder.

[0090] The extruded multilayer film is dried at an oven temperature in the range of about 95° C. to about 150° C. The self-supporting film is peeled from the belt and heated in a tenter oven with a radiant heater at a temperature of about 110° C. to about 805° C. (radiant heater surface temperature) to completely dry and imidize the polymer. Examples 1 and 3

[0091] For Examples 1 and 3 (E1 and E3), the core polymer composition contains a polyimide derived from a dianhydride and a diamine in an approximately 1:1 molar ratio, the dianhydride being PMDA, and the diamine being ODA. The thermoplastic outer layer also contains a polyimide derived from a dianhydride and a diamine in an approximately 1:1 molar ratio. The dianhydride composition contains a 20:80 molar ratio of monomers PMDA and ODPA, and the diamine composition is 100 mole % RODA monomer. The flow rate of the polyamic acid solution is adjusted to produce a three-layer film in which the thermoplastic outer layers are each approximately 6 μm thick and the core layer is approximately 38 μm thick. Example 2

[0092] For Example 2 (E2), the core layer polymer composition contains a polyimide derived from a dianhydride and a diamine in a molar ratio of about 1:1. The dianhydride composition contains a monomer BPDA / PMDA in a molar ratio of 88:12, and the diamine composition contains a monomer PPD / ODA in a molar ratio of 95:5. The thermoplastic outer layer also contains a polyimide derived from a dianhydride and a diamine in a molar ratio of about 1:1. The dianhydride composition contains a monomer PMDA and ODPA in a molar ratio of 20:80, and the diamine composition is 100 mole % RODA monomer. The flow rate of the polyamic acid solution is adjusted to produce a three-layer film, wherein the thermoplastic outer layers are each about 6 μm thick, and the core layer is about 38 μm thick. Comparative Example 1

[0093] For Comparative Example 1 (E1), the core layer polymer composition contains a polyimide derived from a dianhydride and a diamine in a molar ratio of about 1:1. The dianhydride composition contains a 88:12 molar ratio of monomers BPDA / PMDA, and the diamine composition contains a 95:5 molar ratio of monomers PPD / ODA. The thermoplastic outer layer also contains a polyimide derived from a dianhydride and a diamine in a molar ratio of about 1:1. The dianhydride composition contains a 20:80 molar ratio of monomers PMDA and ODPA, and the diamine composition is 100 mole % RODA monomer. The flow rate of the polyamic acid solution is adjusted to produce a three-layer film in which the thermoplastic outer layers are each about 6 μm thick and the core layer is about 38 μm thick. Table 1

[0094] The membranes of E1-E3 contained a carbon black slurry (at an appropriate loading to produce the desired surface resistivity). The membrane of CE1 did not have any conductive filler in any layer.

[0095] The membranes of E1-E3 and CE1 were metallized with copper to form a metal layer on the polymer film and tested as current collectors in a half-cell battery configuration. Prior to metallization, the membrane samples were cut into approximately 5×7” dimensions and clamped in a stainless steel frame. The membrane surface was cleaned using a 2-step plasma process. Cleaning was performed with a N2 / CF4 / O2 mixture at 300 mTorr plasma exposure for 5 minutes, followed by exposure to O2 plasma for 30 seconds. After plasma treatment, the membrane was immersed in a 1 M NaOH aqueous solution at 45°C for 90 seconds with gentle stirring, then rinsed with running tap water for 2 minutes, and directly immersed in the electroplating bath as described below.

[0096] CE1 was prepared by first exposing to the above plasma step and 1 M NaOH bath. Then, without using a desmear step, CIRCUPOSIT TMThe samples were plated using a 6500 electroless copper deposition process and processed as follows: 1. Immerse the membrane in CIRCUPOSIT at pH 2 under gentle stirring at room temperature. TM 6520A Pre-Dip (DuPont de Nemours, Inc., Wilmington, Del.) for 30 seconds. 2. The membrane was then immersed in 200 ppm Pd at 50 °C with gentle stirring. 2+ CIRCUPOSIT made at ion concentration TM 6530 catalyst (DuPont) for 60 seconds. 3. The membrane was then rinsed under running tap water for 60 seconds. 4. Then immerse the membrane in CIRCUPOSIT at 32°C with gentle stirring. TM 6540 reducing agent solution (DuPont) for 60 seconds. 5. The membrane was then rinsed under running tap water for 60 seconds. 6. Then immerse the membrane in CIRCUPOSIT at about 34°C. TM 6550 electroless copper plating bath (DuPont) for 2.5 minutes. 7. The membrane was then rinsed under running tap water for 60 seconds.

[0097] After electroless plating, the films were dried and stored in a desiccator before use in electroplating.

[0098] The chemical plating process forms a copper layer of approximately 80-120 nm on the polyimide film. The chemical plating process is then followed by an electrolytic plating process. For CE1, the chemically plated sample was pre-cleaned as follows before the electrolytic bath: 1. Treat the membrane with RONACLEAN at 40°C. TM Pre-treat with LP-200 cleaner (DuPont) for 120 seconds. 2. The membrane was then rinsed in deionized (DI) water for 120 seconds. 3. The membrane was then treated in 40 g / L sulfuric acid for 30 seconds before being transferred to the electrolytic plating bath. Using MICROFILL TM The EVF-II process electrolytically plated all examples sequentially.

[0099] The copper electroplating bath is prepared by mixing 200 g / L of copper in the form of copper sulfate pentahydrate, 100 g / L of sulfuric acid, 60 ppm of chloride ions, 1.25 ml / L of MICROFILL TM EVF-II XB, 33ml / L MICROFILLTM EVF-II XL and 10ml / L MICROFILL TM EVF-II XC (all DuPont) were combined and prepared. The membrane was electrolytically plated in a 5.5L plating tank with air agitation set to 2 LPM and the temperature controlled at 75°F (24°C) by a heated water bath. The membrane was removed from the desiccator, mounted between two 5" x 7" stainless steel frames with 4.5" x 5.5" windows and processed as follows: 1. The films were plated in a bright acid copper bath at a current density of 5 ASF to achieve a target thickness of 1 μm. 2. After electrolytic copper plating, rinse the membrane with DI water for 120 seconds, remove it from the frame, and immerse it in ANTITARNISH TM 7130 (DuPont) for 15 seconds, rinse with DI water for 30 seconds, and dry in air.

[0100] To prepare half-cell cells, graphite electrodes were prepared by applying a graphite slurry to a current collector in contact with the membrane layer using a scraper. The graphite slurry was prepared from battery-grade graphite powder, Super P carbon black (Imerys SA, France), and styrene butadiene rubber (SBR) binder in a weight ratio of 95.7:1.5:2.8 (graphite: SuperP carbon black: SBR binder), mixed with a magnetic stirrer for approximately 24 hours to form a 46 wt% solid slurry in water. After coating on the current collector, the assembly was dried in a convection oven at 70°C for at least 24 hours before use. The loading of graphite active components on the electrode was 5 mg (total solids) / cm 2 , or 5*0.957=4.785g graphite / cm 2 3 / 8" discs were punched out of the electrodes for cell evaluation. 0.25 mm (10 mil) thick lithium metal foil (Aldrich, Milwaukee, WI) was used as the counter electrode in half-cell measurements. As with the graphite electrodes, 3 / 8" discs were used.

[0101] The half-cell battery is prepared in the form of a button cell and uses The separator 2325 (Celgard, LLC., Charlotte, NC), a lithium foil counter electrode (thickness 0.25 mm), a graphite electrode, and a few drops of a non-aqueous electrolyte composition (1M LiPF6 EC / EMC / DMC, 1:1:1 by volume) obtained from Aldrich were assembled. The lithium foil counter electrode, graphite electrode, and separator and anode were stacked and sandwiched in a 2032 stainless steel coin cell can (MTI, California) to form a half-cell in an argon-filled dry box. For the tests, all C rates were calculated based on an assumed charge capacity of 300 mAh / g. Therefore, each coin cell battery had an assumed capacity of 1.44 mAh. All measurements were performed at 25°C. The battery was cycled at a charge rate of 0.1C, and in subsequent cycles, the discharge rate was increased from 0.1C to 0.2C, 1C, 2C, and 5C.

[0102] For each discharge cycle, the intermediate discharge voltage (the voltage at which half of the charge capacity of the cell is reached during discharge) was determined from the discharge curve. This was used to characterize the polarization of the cell, which is related to the internal resistance of the cell. 2-3 coin cell cells were prepared from each current collector. The average intermediate discharge voltages of the current collectors at 2C and 5C are shown in Table 1. For CE2, 9 μm battery grade copper foil (with a purity greater than 99.95%, 0.168 ohm-g / m 2 The resistivity, surface roughness less than 0.4μm and 41kg / m 2 of tensile strength) was used as a current collector in the same half-cell configuration used in other examples. Table 1 Examples 2C 5C E1 0.271 0.473 E2 0.349 0.636 E3 0.285 0.486 CE1 0.463 0.657 CE2 0.543 0.863

Claims

1. A current collector comprising a polymer film, a first metal layer adhered to the polymer film, and a second metal layer adhered to the polymer film on a side opposite to the first metal layer, wherein: The polymer film comprises a conductive filler and has a surface resistivity of 1 megohm / square or less; The first metal layer and the second metal layer each have a thickness of 3 μm or less; and The current collector has an intermediate discharge voltage that is at least 20% lower when compared to untreated battery grade copper foil based on a standard lithium ion battery half-cell test conducted at a temperature of 25°C and a discharge rate of 2C or higher.

2. The current collector according to claim 1, wherein: The polymer film includes a polymer containing imide groups.

3. The current collector according to claim 1, wherein: The polymer film comprises a multilayer film, the multilayer film comprising: a first outer layer comprising a first polymer; a second outer layer comprising a second polymer; and A core layer comprising a third polymer, wherein the core layer is between the first outer layer and the second outer layer, and the conductive filler is present in one or more of the layers.

4. The current collector according to claim 3, wherein: One or more of the first polymer, the second polymer, and the third polymer include a polymer including an imide group.

5. The current collector according to claim 1, wherein: The conductive filler is present in the polymer film at a concentration ranging from 5 to 65 weight percent based on the total weight of the polymer film. An energy storage device comprising the current collector according to claim 1 .

7. The energy storage device according to claim 6, wherein: The energy storage device is selected from the group consisting of: a lithium-ion battery, a capacitor, a supercapacitor, a fuel cell unit, and a redox flow battery.

Citation Information

Patent Citations

  • Nonaqueous electrolyte compositions

    US20160087307A1

  • Process for preparing shaped articles from polyamide acids before converting to insoluble polyimides

    US3410826A

  • Copolyimide film with improved properties

    US5166308A

  • Flexible multi-layer polyimide film laminates and preparation thereof

    US5298331A

  • Positive electrode active material for lithium battery

    US5738957A

Cited By

  • PET-based composite copper foil as well as preparation method and application thereof

    CN120425326A